2019
DOI: 10.1016/j.ijheatmasstransfer.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Elliptical double corrugated tubes for enhanced heat transfer

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…The impact of the corrugation period K and aspect ratio AR on the thermo-hydraulic performance of the double corrugated tubes has been analyzed using CFD software. The modeling results have been reported in Navickaite et al (2019a), and in that article it was demonstrated that in the low Reynolds number region the double corrugated tubes with shorter corrugation period K are more effective (Navickaite et al, 2019a). Moreover, increasing thermal efficiency was obtained for double corrugated tubes with increasing AR up to 2.2.…”
Section: Amr Geometriesmentioning
confidence: 86%
See 1 more Smart Citation
“…The impact of the corrugation period K and aspect ratio AR on the thermo-hydraulic performance of the double corrugated tubes has been analyzed using CFD software. The modeling results have been reported in Navickaite et al (2019a), and in that article it was demonstrated that in the low Reynolds number region the double corrugated tubes with shorter corrugation period K are more effective (Navickaite et al, 2019a). Moreover, increasing thermal efficiency was obtained for double corrugated tubes with increasing AR up to 2.2.…”
Section: Amr Geometriesmentioning
confidence: 86%
“…Moreover, the simulations were performed using constant pressure drop conditions that were normalized to the length of modeled tubes. This implies that the mass flow rate passing through the tubes varied (Navickaite et al, 2019a).…”
Section: Amr Geometriesmentioning
confidence: 99%
“…The experimental and CFD simulation results on double corrugated tube geometry were first presented in [20,21], respectively. There, the enhancement of the heat transfer was numerically and experimentally analysed for internal flow.…”
Section: Methodsmentioning
confidence: 99%
“…There, the enhancement of the heat transfer was numerically and experimentally analysed for internal flow. The double corrugation of the tube wall was shown to break up the thermal boundary layers and hinder their development, thus increasing the heat transfer through the tube wall at a reasonable increase in pressure drop [20,21]. The geometry of these double corrugated tubes mimics the blood vessels in counter flow heat exchangers existing in warm-blooded fish [27] and those fish species that are able to maintain their regional body temperature higher than that of their living environment [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation